Kynurenic Acid and Its Analogue SZR-72 Ameliorate the Severity of Experimental Acute Necrotizing Pancreatitis - Balla, Zsolt; Kormányos, Eszter Sára; Kui, Balázs; Bálint, Emese Réka; Fűr, Gabriella; Orján, Erik Márk; Iványi, Béla; Vécsei, László; Fülöp, Ferenc; Varga, Gabriella; Harazin, András; Tubak, Vilmos; et al. (Frontiers in Immunology, 2021)
The pathophysiology of acute pancreatitis (AP) is not well understood, and the disease does not have specific therapy. Tryptophan metabolite L-kynurenic acid (KYNA) and its synthetic analogue SZR-72 are antagonists of the N-methyl-D-aspartate receptor (NMDAR) and have immune modulatory roles in several inflammatory diseases. Our aims were to investigate the effects of KYNA and SZR-72 on experimental AP and to reveal their possible mode of action. AP was induced by intraperitoneal (i.p.) injection of L-ornithine-HCl (LO) in SPRD rats. Animals were pretreated with 75-300 mg/kg KYNA or SZR-72. Control animals were injected with physiological saline instead of LO, KYNA and/or SZR-72. Laboratory and histological parameters, as well as pancreatic and systemic circulation were measured to evaluate AP severity. Pancreatic heat shock protein-72 and IL-1β were measured by western blot and ELISA, respectively. Pancreatic expression of NMDAR1 was investigated by RT-PCR and immunohistochemistry. Viability of isolated pancreatic acinar cells in response to LO, KYNA, SZR-72 and/or NMDA administration was assessed by propidium-iodide assay. The effects of LO and/or SZR-72 on neutrophil granulocyte function was also studied. Almost all investigated laboratory and histological parameters of AP were significantly reduced by administration of 300 mg/kg KYNA or SZR-72, whereas the 150 mg/kg or 75 mg/kg doses were less or not effective, respectively. The decreased pancreatic microcirculation was also improved in the AP groups treated with 300 mg/kg KYNA or SZR-72. Interestingly, pancreatic heat shock protein-72 expression was significantly increased by administration of SZR-72, KYNA and/or LO. mRNA and protein expression of NMDAR1 was detected in pancreatic tissue. LO treatment caused acinar cell toxicity which was reversed by 250 µM KYNA or SZR-72. Treatment of acini with NMDA (25, 250, 2000 µM) did not influence the effects of KYNA or SZR-72. Moreover, SZR-72 reduced LO-induced H2O2 production of neutrophil granulocytes. KYNA and SZR-72 have dose-dependent protective effects on LO-induced AP or acinar toxicity which seem to be independent of pancreatic NMDA receptors. Furthermore, SZR-72 treatment suppressed AP-induced activation of neutrophil granulocytes. This study suggests that administration of KYNA and its derivative could be beneficial in AP.